Use of drug-coated balloons in the management of a recalcitrant postsurgical hepatic vein stenosis in a pediatric patient - Dimitri A. Parra, MD; Leonardo Brandao, MD (Radiology Case Reports, 2020)
Drug-coated balloons (DCB) are a treatment alternative to conventional angioplasty in arterial, hemodialysis fistulas, and venous stenoses. This case report describes a child with the diagnosis of hepatoblastoma treated with chemotherapy and a right extended hepatectomy with venous reconstruction. The patient presented with signs and symptoms of portal hypertension due to a hepatic venous outflow obstruction secondary to stenosis of the surgical anastomosis. The response to conventional angioplasty was limited with frequent recurrence of symptoms. DCBs were used as an alternative prior to stent consideration aiming to assess if these devices could provide improvement of the symptoms and as a long-term therapy. The use of DCBs increased the time interval of reinterventions in comparison with conventional angioplasty. The patient eventually required stents due to recurrence of the primary disease.While this report does not provide an in-depth evaluation in terms of the efficacy and safety of DCB, this case illustrates a potential novel treatment modality to be considered for children, when stenotic venous lesions not amenable for stenting are present.